An integrative review exploring the experiences of service users carrying a diagnosis of personality disorder and student mental health nurses and the time they share together. (March 2021) - Jones, Emma; Wright, Karen M.; McKeown, Mick
Abstract: Objectives: This integrative review provides a collective understanding of the experiences of student mental health nurses and service users carrying a diagnosis of personality disorder and the time they share together. Design: Published studies about the time service users and students share together were systematically selected in order to integrate their findings in a thematic analysis. Data sources: Various databases were searched from 1984 until 2020. Specific search terms were used. Review methods: 37 studies were included in the integrative review. The studies were from peer reviewed nursing, student, psychology and health related journals. A quality appraisal was completed using Walsh and Downe (2006) framework. Findings: Four themes emerged from a thematic analysis of the integrative review. These were; 1. 'Psychosocial skills' 2. 'Relationships' 3. 'Environment' With 'Impact of time' as an overarching theme. Conclusion: A positive environment which considers time and focuses on seeing the person, as an individual can lead to the development of therapeutic relationships; a core element of the Nursing and Midwifery Council standards for nursing registration in the UK (Nursing and Midwifery Council, 2018 ). Students attempting to build such relationships need to be mindful of service users' and their own attachment experiences and the impact these can have on experiences of transference and countertransference, particularly for service users carrying a personality disorder diagnosis. It is important for students to be aware of the supportive impact of positive environments and how doing ' everyday stuff' can make a person feel human despite residing in potentially dehumanizing places. Highlights: An environment which considers time and focuses on seeing the person, can lead to the development of therapeutic relationships. Students attempting to build such relationships need to be mindful of service users' and their own attachment experiences. It is important for students to be aware of the supportive impact of positive environments. Doing 'everyday stuff' can make a person feel human despite residing in potentially dehumanizing places.